2010
DOI: 10.1590/s0037-86822010000400004
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of cytomegalovirus antibodies in blood donors in southern, Brazil

Abstract: Introduction: Cytomegalovirus (CMV) infection is a matter of concern for blood bank professionals and blood transfusion recipients, especially in cases of transfusions to neonates and immunocompromised patients. Thus, the present study aimed to determine the seroprevalence of CMV IgG and IgM antibodies among blood donors in the City of Lages, in the mountain region of Santa Catarina, southern Brazil, and to investigate possible associations between the socioeconomic characteristics of donors and CMV serologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
27
4
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 4 publications
8
27
4
3
Order By: Relevance
“…This differs from previous studies, in which this antibody was more prevalent in older age ranges Brazil studies which showed a significantly increased seropositivity with increasing age of blood donors [14]. This may possibly due to earlier acquisition of CMV infection in Yemen in childhood compared to the western populations, leading to higher seroprevalence even in younger adults [10,19].…”
Section: Resultscontrasting
confidence: 86%
See 2 more Smart Citations
“…This differs from previous studies, in which this antibody was more prevalent in older age ranges Brazil studies which showed a significantly increased seropositivity with increasing age of blood donors [14]. This may possibly due to earlier acquisition of CMV infection in Yemen in childhood compared to the western populations, leading to higher seroprevalence even in younger adults [10,19].…”
Section: Resultscontrasting
confidence: 86%
“…The seropositive for CMV IgG antibodies among Yemeni blood donors was 96.6% indicating past exposure to infection the high seroprevalence in Yemen and developing countries as India, Brazil and Nigeria is in contrast to Western literature which describes seroprevalence IgG in voluntary blood donors ranging from 38% to 75% in different parts of the developed world [13][14][15]. The high seroprevalence among Yemeni populations indicates the endemicity of infection.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…However, CMV is more common in developing countries and in people belonging to lower socio-economic status (Ojide et al, 2012;Arun et al, 2012). The seroprevalence of CMV is 80 -100% in Africa and Latin America (Souza et al, 2010). Like most other herpes viruses, CMV remains latent in the host after primary infection and persists for life in the organism.…”
Section: Introductionmentioning
confidence: 99%
“…The seroprevalence rates of CMV antibodies among blood donors show geographic differences, ranging from 45.8% in Germany to 96.5% in Brazil (3,7). Primary CMV infections in blood donors occur in all age groups, with prevalence rates between 0.2 and 1.2% (3,6,8,9).…”
mentioning
confidence: 99%